Electromyographic validation of the trapezius and serratus anterior muscles in military press exercises with middle grip - Büll, M. L. [UNESP]; Vitti, M. [UNESP]; Freitas, V. [UNESP]; Rosa, G. J M [UNESP] (My University, 2001)
Electromyographic activity of the trapezius muscle and serratus anterior muscle was analysed in 24 male volunteers using a 2-channel TECA TE 4 electromyograp, during the execution of four different modalities of military press exercises with middle grip. The trapezius acted preferentially in the modalities standing press behind neck; and sitting forward and press behind neck, while SI did not show any significative difference among the modalities. The high levels of action potentials with which TS and SI acted justify the inclusion of these exercises in physical programmes.
Keywords: adult; army; biomedical technology assessment; body position; controlled study; electric activity; electromyography; hand grip; human; human experiment; intercostal muscle; male; muscle action potential; muscle contraction; muscle exercise; normal human; trapezius muscle; validation process; Adult; Electromyography; Humans; Isometric Contraction; Male; Motor Neurons; Muscle, Skeletal; Physical Fitness; Reference Values; Scapula; Signal Processing, Computer-Assisted; Weight Lifting